Islamic Banks Spin-Off Policy in Indonesia: A Sentiment Analysis Approach - Siti Salmah; Devi, Abrista (SMART Insight, 2023)
Government policy related to the Spin off of Islamic Banks is one of the efforts to develop and strengthen the role of Islamic banking. The purpose of this study is to see the extent of development and sentiment towards the Spin Off of Islamic Banks. The method used is descriptive statistical analysis combined with meta-analysis and sentiment from secondary data in the form of metadata from 45 Dimension indexed articles, then processed using Microsoft Excel 2019 and SentiStrenght software. The results of the analysis show that the topic of Islamic Bank Spin off has a neutral sentiment of 46.7% followed by a positive sentiment of 31.1% and a negative sentiment of 22.2%. In addition, factors that influence positive and negative sentiments towards the Islamic Bank Spin off were also found.